Research and design for fashion - Sorger, Richard; Seivewright, Simon (New York : Bloomsbury Visual Arts, 2021)
"Now in its fourth edition, this 'toolkit for inspiration' introduces the research techniques fashion designers use to find and develop ideas for their original collections"--
Includes bibliographical references and index.
Keywords: Fashion design; Fashion design -- Study and teaching